Protective potential of mesenchymal stem cells against COVID-19 during pregnancy - Sihem Aouabdi; Doaa Aboalola; Samer Zakari; Suliman Alwafi; Taoufik Nedjadi; Rawiah Alsiary (Future Science OA)
SARS-CoV-2 causes COVID-19. COVID-19 has led to severe clinical illnesses and an unprecedented death toll. The virus induces immune inflammatory responses specifically cytokine storm in lungs. Several published reports indicated that pregnant females are less likely to develop severe symptoms compared with non-pregnant. Putative protective role of maternal blood circulating fetal mesenchymal stem cells (MSCs) has emerged and have been put forward as an explanation to alleviated symptoms. MSCs with immune-modulatory, anti-inflammatory and anti-viral roles, hold great potential for the treatment of COVID-19. MSCs could be an alternative to treat infections resulting from the SARS-CoV-2 and potential future outbreaks. This review focuses on the MSCs putative protective roles against COVID-19 in pregnant females.